Effect of maceration and mae (microwave assisted extraction) on antioxidant activity of methanol Extract of simpur air leaves (dillenia suffruticosa (griff.) martelli) - Isnindar Isnindar; Siti Nurhayati; Sri Luliana; Meri Ropiqa (Universitas Gadjah Mada, 2025)
The simpur air plant (Dillenia suffruticosa) is one of the plants used in traditional medicine to treat various diseases and has potential as an antioxidant. Antioxidants are compounds that inhibit, prevent, and reduce oxidative damage to target molecules. The effectiveness of extracting active compounds depends on the extraction method used. Maceration requires a relatively long duration, so faster and more efficient alternatives, such as MAE, are needed. However, heat-sensitive compounds may degrade if the power is too high or the extraction time is prolonged. Therefore, a comparison between maceration and MAE methods is necessary. This study aims to determine the effect of maceration and MAE on the antioxidant activity of the methanol extract from the simpur air leaves. Samples were then analyzed using TLC with a mobile phase of toluene, ethyl acetate, and formic acid (3:5:1 v/v/v). Antioxidant activity was assessed using the DPPH (2,2-diphenyl-1-picrylhydrazyl) assay, and data were analyzed with SPSS. TLC results confirmed the presence of flavonoids indicated by a yellow color after spraying with AlCl3, with IC50 values supporting their antioxidant potential. The Rf values of extracts obtained by maceration and MAE with the rutin standard (0.22) and quercetin standard (0.8). The MAE method produced higher antioxidant activity than maceration, with IC₅₀ values of 5.942 ± 0.345 μg/mL and 10.498 ± 0.213 μg/mL, respectively, both classified as strong antioxidants (IC50 < 50). Independent sample t-test analysis yielded a p-value of less than 0.05, indicating a significant difference between the two methods. The methanol extract of simpur air leaves extracted by the MAE method produces better antioxidant activity than the maceration method.